Historical stages of the Koeppen climate classification and trying to modify it. - علي خضر, سالار (Al-Adab Journal, 2018)
The Koeppen Climate Classification is one of the classifications that has facilitated the understanding of the geographical distribution of climatic regions around the world. It is based on very simple mathematical equations, as well as on the two most important climatic elements (temperature and rain) measured in all climate stations around the world. Despite the importance of this classification, but the most important problem is the collection of several climatic stations within one climatic region, although there are significant differences in (temperature and rain) between these stations, so This research try to find a solution to this problem by presenting a climate classification complements the Koeppen climate classification in the form of a diagram based on annual and general averages for both temperature and rainfall. The climate classification included (4) major climatic varieties and (5) transitional climates, Total (9) Climatic varieties.This classification provides many advantages, including the classification of the limited areas of the region, and classifies the main climates such as the desert climate (Koeppen classification) to different climatic varieties, so that it determines the best sections of the desert climate, and it is characterized as continuity, in the sense that the classification can be applied several times down To determine the best climatic varieties.